Geographical Dispersion and Investment Efficiency. Issue 7 (28th May 2022) - Wang, Junjie; Liu, Chen; Pan, Yichen; Liu, Siyi
ABSTRACT: Our study reconciles the mixed effects of geographical dispersion within corporations on investment efficiency based on listed firms in China from 2007–2019. The results show that geographical dispersion of subsidiaries can effectively improve the overall investment efficiency for the corporation, which support the hypothesis of mitigating the attenuation effect of operating distance. Then, we carry out cross-sectional tests from the perspectives of information transfer costs and institutional differences. The results show that the above influence is more significant when either the parent and subsidiary firms are not located in the high-spee5d rail network or the institutional background difference between the parent and subsidiary firms is big. After controlling the endogenous problem and measurement error, the baseline results remain the same. Furthermore, we verify the inverted U-shaped relationship between geographical dispersion and investment efficiency. The conclusions not only supplement the related literature on geographical distance and investment efficiency, but also provide important inspiration for management, policy makers.